Comparative study on the future of combustion and emissions of internal combustion heavy duty engines with dual-fuel, diesel/hidrogen - Lopes Frazão, Jorge Miguel (My University, 2024)
In this work, a comparative study on the effects of partial replacement of diesel by hydrogen in fuel efficiency, energy substitution, volumetric efficiency and exhaust emissions of a dual fuel engine fueled with diesel/hydrogen was conducted experimentally. The experiments were conducted at fixed speeds of 1000, 1250, 1500, 1750 and 2000 rpm at no load. The hydrogen was injected in admission port alt flows ranging from 1 to 15 l/min. The results indicated that adding hydrogen influenced fuel economy, with savings from 6.2% to 28.2% depending on the engine's rpm. It was also registered an increase in volumetric efficiency of 23.4% with less 50% CO and 83% NOx. Nevertheless, the total energy input decreased 17% at 2000 rpm and 15 l/min ofH2.
Keywords: Dual-Fuel; Hydrogen; Heavy-Duty machinery; Non-Road Mobile machinery; NRMM; GHC Emissions; Mining; Quarrying